Unusual combination of Bado type I Monteggia lesion and ipsilateral humerus lateral condyle fracture with intercondylar extension in an adult following high velocity trauma: a case report - Lokesh, Sachin Patel; Veeranna, Goutham Doddanna; Channarayapatana Devaraj, Deepak; Gorkal , Avinash (International Journal of Research in Orthopaedics, 2025)
Monteggia fracture dislocation is a rare injury pattern which accounts for less than 2% of all forearm fractures (in both adults and children) and accounts for 0.7% of all elbow fractures and dislocations in adults. The present case involves a 22-year-old male with Bado type I Monteggia fracture dislocation with ipsilateral lateral condyle humerus fracture with intercondylar extension with no distal neurovascular deficits which is the first case to be reported in literature to the best of our knowledge. A successful outcome was achieved due to early diagnosis, anatomical reduction, stable internal fixation and early mobilization. This case report aims to highlight this rare presentation and in adding data to literature for describing this injury pattern in Bado type I equivalents. These injuries require a comprehensive clinical and radiological evaluation for diagnosis as well as management.